PENGARUH DEBT TO EQUITY RASIO (DER), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) DAN FINACING TO DEPOSIT RATIO (FDR) TERHADAP RETURN ON ASSETS (ROA) PADA BANK BTPN SYARIAH PERIODE TAHUN 2012-2021 - Yeni Yuli Yanti (Jurnal Enterpreneur dan Bisnis (JEBI), 2024)
Sharia Banking is one of the benchmarks for the application of the concept of Sharia Economics in Indonesia, because Sharia Banking is one of the solutions to the nation's economy. Bank BTPN Syariah is one of the financial institutions that has a strategic role, namely through its function as an institution that collects funds from the public and then distributes these funds to people in need. BTPN Syariah also has the main objective of making a profit or profit by increasing the profitability or profit of its business. The purpose of this study was to determine the effect of debt to equity ratio (DER), operating expenses and operating income (BOPO) and financing to deposit ratio (FDR) have a direct influence on return on assets (ROA) at Bank BTPN Syariah period 2012- 2021. This study uses secondary data types with quantitative research methods and uses 40 samples of BTPN Syariah Bank financial reports. Based on the results of the study, it is known that the financing to deposit ratio (FDR) has no effect on return on assets (ROA) while the debt to equity ratio (DER) and operating expenses and operating income (BOPO) have a positive and significant effect on return on assets (ROA). ) at Bank BTPN Syariah for the period 2012-2021. Taken together, the effect of the Debt To Equity Ratio (DER), Operational Cost of Operating Income (BOPO) and Finacing To Deposit Ratio (FDR) have an effect of 21.1% on the Return On Assets (ROA) at Bank BTPN Syariah for the period of 2012- 2021. While the remaining 78.9% is influenced by other factors not examined in this study.